Annular lipoatrophy of the ankle: Four new pediatric cases and a review of the literature. Issue 5 (21st August 2021) - Touhouche, Timila Assia; Tournier, Emilie; Lamant, Laurence; Hardy, Juliette; Taieb, Alain; Labreze, Christine; Cony, Marianne; Lepreux, Sebastien; Chiaverini, Christine; Lacour, Jean Philippe; Cardot‐Leccia, Nathalie; Bedane, Christophe; et al.
Abstract: Annular lipoatrophy of the ankle is a rare and unique acquired lipoatrophic panniculitis that mainly affects children. There is no consensus on treatment, and the long‐term course is not well known. We present four new pediatric cases that contribute to the understanding of this rare disease.